Molecular investigation of haemotropic mycoplasmas and Coxiella burnetii in free-living Xenarthra mammals from Brazil, with evidence of new haemoplasma species - de Oliveira, Laryssa Borges [UNESP]; Calchi, Ana Cláudia [UNESP]; Vultão, Juliana Gaboardi; Yogui, Débora Regina; Kluyber, Danilo; Alves, Mário Henrique; Desbiez, Arnaud Leonard Jean; de Santi, Mariele [UNESP]; Soares, Aline Girotto; Soares, João Fabio; Werther, Karin [UNESP]; Teixeira, Marta Maria Geraldes; et al. (Hindawi, 2022)
Although mammals of the superorder Xenarthra are considered hosts of a wide range of zoonotic agents, works aiming at investigating the role of these animals as hosts for bacteria with zoonotic potential are rare. The present study aimed to investigate the occurrence and molecularly characterize Coxiella burnetii and haemoplasma (haemotropic mycoplasmas) DNA in blood and spleen samples from 397 free-living Xenarthra mammals (233 sloths, 107 anteaters and 57 armadillos) in five Brazilian states (Mato Grosso do Sul, São Paulo, Pará, Rondônia and Rio Grande do Sul). All biological samples from Xenarthra were negative in the qPCR for Coxiella burnetii based on the IS1111 gene. The absence of C. burnetii DNA in blood and spleen samples from Xenarthra suggests that these mammals may not act as possible hosts for this agent in the locations studied. When performed conventional PCR assays for the endogenous (gapdh) mammalian gene, 386 samples were positive. When screened by molecular assays based on the 16S rRNA gene of haemoplasmas, 81 samples were positive, of which 15.54% (60/386) were positive by conventional PCR and 5.44% (21/386) were positive by real-time PCR; three samples were positive in both assays. Of these, 39.74% (31/78) were also positive for the 23S rRNA gene and 7.69% (6/78) for the haemoplasma RNAse P gene. Among the samples positive for haemoplasmas, 25.64% (20/78) were obtained from anteaters (Tamandua tetradactyla and Myrmecophaga tridactyla), 39.74% (31/78) from sloths (Bradypus tridactylus, Bradypus sp. and Choloepus sp.) 34.61% (27/78) from armadillos (Priodontes maximus, Euphractus sexcinctus and Dasypus novemcinctus). A haemoplasma 16S rRNA sequence closely related and showing high identity (99.7%) to Mycoplasma wenyonii was detected, for the first time, in B. tridactylus. Based on the low identity and phylogenetic positioning of 16S rRNA and 23S rRNA sequences of haemoplasmas detected in anteaters and armadillos, the present study showed, for the first time, the occurrence of putative new Candidatus haemotropic Mycoplasma spp. (“Candidatus Mycoplasma haematotetradactyla” and “Candidatus Mycoplasma haematomaximus”) in Xenarthra mammals from Brazil.
Keywords: anteaters; armadillos; haemoplasmas; Q-fever; sloths